Analisis Perubahan Tutupan Lahan di Kabupaten Manokwari Selatan - Silvy E. Kesaulija; Agustinus Murdjoko; Soetjipto Moeljono (Cassowary, 2020)
This study aims to determine the extent of land cover changes in South Manokwari Regency from 2009 to 2018, including what changes have occurred, where they have occurred, how much change has occurred and the factors causing forest area changes in South Manokwari Regency. The method used in this research was the overlay technique with the supervised classification method. Data collection and analysis were carried out spatially using ArcGIS 10.4 software. The research variables consisted of forest area and land cover in hectares, changes in land cover (deforestation and degradation) in hectares and factors that influenced changes in land cover in South Manokwari Regency. The analysis of land cover based on area functions, permits and district boundaries, found that there had been degradation and eforestation in South Manokwari Regency. The area of ​​forest degradation is 8,870.15 Ha that occurs inside the Production Forest in the IUPHHK concession area in Dataran Isim District. Meanwhile, the deforestation of 1,357.75 hectares occurred in other use areas. Other factors that influence land cover change were accessibility factors, government policies and topographical factors.